Challenges when working with renewable materials: knocking on wood?. Issue 6 (2nd November 2021) - Henriksson, Fredrik; Johansen, Kerstin; Schütte, Simon
ABSTRACT: With sustainable design as a vital strategical component for companies competing on the market today, many companies will need to transition to a use of sustainable and/or renewable materials in the near future. But how can this be done, and what can be done to bridge the gap from current affairs to a new, more sustainable state? Looking towards industries with experience might help making the first step just a little bit easier. This study aims to find challenges and bottlenecks when working with sustainable materials, in order to help companies interested in transitioning towards using sustainable or renewable materials in their products. The paper describes an interview study with five Swedish wood industry companies, differentiated in size and products, where the authors identify several key findings for both industry (already working with wood or aiming at transitioning towards renewable materials) and academia (on using renewable materials, need for further research, and pointers for teaching design and engineering students). Findings range from how organisational culture affects material selection, to how flexibility and efficiency effects automation solutions via how these companies have approached outsourcing of parts of their production.